2020
DOI: 10.1124/dmd.120.000202
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Volume of Distribution in Humans: Performance of In Silico Methods for a Large Set of Structurally Diverse Clinical Compounds

Abstract: Volume of distribution at steady state (V D,ss) is one of the key pharmacokinetic parameters estimated during the drug discovery process. Despite considerable efforts to predict V D,ss , accuracy and choice of prediction methods remain a challenge, with evaluations constrained to a small set (<150) of compounds. To address these issues, a series of in silico methods for predicting human V D,ss directly from structure were evaluated using a large set of clinical compounds. Machine learning (ML) models were buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This result is aligned with recent publications , and may be explained by additional variability and complexity of oral PK studies, where compounds’ solid form, applied dose, and formulation play a major role in final outcomes. Compared to recently developed computational models based on comparable data sets, our ML models showed similar, ,,,, improved, , or decreased performance. For example, if focusing on the drug-design stage results (i.e., in the absence of in vitro data), Obrezanova et al showed RMSLE values of 0.35, 0.31, and 0.57 for predictions of rat CLp, Vss, and oral F, respectively .…”
Section: Discussionmentioning
confidence: 65%
“…This result is aligned with recent publications , and may be explained by additional variability and complexity of oral PK studies, where compounds’ solid form, applied dose, and formulation play a major role in final outcomes. Compared to recently developed computational models based on comparable data sets, our ML models showed similar, ,,,, improved, , or decreased performance. For example, if focusing on the drug-design stage results (i.e., in the absence of in vitro data), Obrezanova et al showed RMSLE values of 0.35, 0.31, and 0.57 for predictions of rat CLp, Vss, and oral F, respectively .…”
Section: Discussionmentioning
confidence: 65%
“…Systemic clearance ( CL ) and volume of distribution ( V ss ) are critical PK parameters. CL describes how fast the drug would be eliminated from the blood; V ss describes the relationship between drug concentration measured in plasma or blood to the amount of drug in the body at equilibrium ( Murad et al, 2021 ). CL together with V ss , can be used to estimate elimination half-life and mean residence time, which define the concentration–time profile of a drug if it is administered via IV bolus.…”
Section: Discussionmentioning
confidence: 99%
“…The extrapolated volume of distribution (0.101 L) was close to the observed value (0.0924 L) in the rat PBPK model. Meanwhile, we also attempted to apply methods by Poulin and Thei, Rodgers, and Lukacova to fit V ss ( Poulin and Theil, 2002 ; Rodgers and Rowland, 2007 ; Murad et al, 2021 ). Results showed that all the predicted V ss values of ST-246 from the three methods dramatically overestimated the observed values.…”
Section: Discussionmentioning
confidence: 99%
“…A compound with Papp more than 8x10 -6 cm/s is considered to have a high Caco2-2 permeability value [56]. All ligands were not able to present high Caco-2 permeability.…”
Section: B Admet Predictionmentioning
confidence: 99%